The Influence of Customer Value, Corporate Image, and Service Innovation towards Customer Satisfaction - Wedhia Ganiesa; Abror Abror; Firman Firman (Jurnal Praktik Bisnis, 2019)
This research aims to analyze: (1) The effect of customer value on customer satisfaction of Britama’ s customer BRI Bank branch of Padang (2) The effect of corporate image on customer satisfaction of Britama’ s customer BRI Bank branch of Padang (3) The effect of service innovation on customer satisfaction of Britama’ s customer BRI Bank branch of Padang. The population in this study is all Britama’ s customers of BRI Bank branch of Padang totaling 8342 people. The sample is 150 people using accidental sampling technique. The results showed that: (1) customer value has a positive effect and significant on customer satisfaction (2) corporate image has a positive effect and significant on customer satisfaction (3) service innovation has a positive effect and significant on customer satisfaction. The conclusion is customer value, corporate image, service innovation have significant effect on customer satisfaction. Service innovation has higher influence on customer satisfaction in this research. For the future research is better to explore more about variable that can inluence customer satisfaction.